Wykorzystanie teatru w edukacji etycznej - Kostyra, Marcin (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2015)
It is difficult to find tools useful for effective teaching ethics focused on persons from disadvantaged groups, which have conflict with the law. Traditional lecture seems to be a boring talk. Theatre can be a more favourable method. An article describes the idea of functioning of the Theatre of Moral Anxiety, founded by author of the article. Actors in this theatre, ‘angry young man’, carry out spectacles based on scripts written explicitly for them, often related to their biographies. Young man recognize and break their own limitations, learn how to cooperate and reveal the world their better human face: sensitivity and involvement. Author shows, that theatre can be wonderful tool of ethical education, raising self-esteem and self-confidence of persons participating in a performance.
Taking advantage of using theatre in teaching ethics
Keywords: theatre; the Theatre of Moral Anxiety; teaching of ethics; philosophy; educationally neglected youth; resocialization; education of young offenders